AN ANALYSIS OF DIFFERENT POLITENESS EXPRESSION IN SHOWING APOLOGIZING - ., Humaira; Lamusiah, Siti (JURNAL SMART, 2016)
This study supposes to know the different expression of the students when they showing apologizing and also analyze more deeply about their culture background. It is affected their apologizing expression or not. It analyzed by descriptive qualitative approach with 19 students from different culture as participant in Postgraduate State University of Semarang. The results of analysis are; every culture differs from each other in their politeness of showing apologizing even though not really significant. Different background of culture is one of the important things that make people differ in particular expression.Key words: politeness, apologizing, expression, and expressive speech act.